2010
DOI: 10.1152/jn.01051.2009
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Rapidly Restores Axonal Integrity and Improves the Rate of Motor Behavior Recovery After Sciatic Nerve Crush Injury

Abstract: MY, Estler CJ, Boydston EA, Schallert T, Bittner GD. Polyethylene glycol rapidly restores axonal integrity and improves the rate of motor behavior recovery after sciatic nerve crush injury. J Neurophysiol 104: 695-703, 2010. First published May 5, 2010 doi:10.1152/jn.01051.2009. The inability to rapidly (within minutes to hours) improve behavioral function after severance of peripheral nervous system axons is an ongoing clinical problem. We have previously reported that polyethylene glycol (PEG) can rapidly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(115 citation statements)
references
References 47 publications
8
103
3
1
Order By: Relevance
“…Latency to fall was calculated for each speed. Details of the grip strength and foot slip tests (43) are provided in SI Appendix, Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Latency to fall was calculated for each speed. Details of the grip strength and foot slip tests (43) are provided in SI Appendix, Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary studies have been promising demonstrating a small improvement in gait function after nerve crush injury (axonotmesis) and a 13-fold improvement after neurotmesis injury, compared to standard of care microsurgery [70, 71]. A recent study reported that compound action potentials could be recorded distal to a 10-mm nerve graft repair up to 7 days after surgery [72].…”
Section: Translational Research In Peripheral Nerve Repairmentioning
confidence: 99%
“…For example, neurons that seal plasmalemmal disruptions at sites nearer to the soma are less likely to survive compared to neurons that seal damage at sites farther from the soma (Ramon y Cajal, 1928;Loewy and Shader, 1977;Lucas et al, 1985Lucas et al, , 1990Yoo et al, 2004;Nguyen et al, 2005). Limiting Ca 2ϩ influx by increasing the rate of plasmalemmal sealing could increase the survival rate of injured neurons (i.e., provide neuroprotection), potentially increasing behavioral recovery following traumatic injury to the CNS or PNS neurons (Britt et al, 2010;Nehrt et al, 2010). Increasing plasmalemmal sealing also decreases the adverse affects of treadmill climbing in normal mice and in a mouse model of muscular dystrophy (Bansal and Campbell, 2004).…”
Section: Clinical Importance Of Plasmalemmal Sealingmentioning
confidence: 99%